SUSTAINING RURAL LIVELIHOOD THROUGH ENTREPRENEURSHIP AND CREATIVE VILLAGE DEVELOPMENT: MALAYSIA AND INDONESIA EXPERIENCE - Khairul Hisyam KAMARUDIN; Rustina UNTARI; Mohamad Fadhli RASHID (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Rural development in various countries in Asia has experienced tremendous change and transformation. Countries like Malaysia and Indonesia have experienced growing interest in utilising information and communication technologies (ICTs) for rural development. ICT and society could create a new pathway for the rural area and its society should progress in future. Evidently, technologies will continue to evolve and used to improve productivity. However, in the long run, this might jeopardise any effort for creating and sustaining employment/job and wealth creations for locals and for rural economic sectors. This is because current jobs including in rural small and medium enterprises (SMEs) could be replaced by technologies, hence might reduce industry dependency on local workforce. There are cases whereby the ICTs and other emerging technologies which have been introduced in rural areas, as shown in “creative kampung” communities, have not deter locals from being employed in rural economic sectors (and SMEs) instead sustaining jobs and improve SMEs operations and productivities. Creative kampung emphasises on sustaining economic activities based on human creativity and/or creative industry that cannot be replaced by machines or any other means of modern technologies. However, it is a norm for local entrepreneurs to incorporate some elements of technologies to improve productivity and quality of products and services, while maintaining the authenticity of their products. The paper presents some key findings based on comparative study of two creative kampungs in Sayong, Kuala Kangsar, Malaysia and Gemawang Village at Semarang District, Central Java Indonesia. It is expected that the findings might have values particularly in improving the understanding on the concept of creative kampung from different localities, internal and external key drivers for transformation of creative kampung and entrepreneurship development.